Hardy Uncertainty Principle for Low Dimensional Nilpotent Lie Groups G4 (III) - Bhatta, CR (Kathmandu University Journal of Science, Engineering and Technology, 2010)
An uncertainty principle due to Hardy for Fourier transform pairs on ℜ says that if the function f is "very rapidly decreasing", then the Fourier transform can not also be "very rapidly decreasing" unless f is identically zero. In this paper we state and prove an analogue of Hardy's theorem for low dimensional nilpotent Lie groups G4. Keywords and phrases: Uncertainty principle; Fourier transform pairs; very rapidly decreasing; Nilpotent Lie groups. DOI: 10.3126/kuset.v6i1.3315 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp89-95